تاثير التسويق الداخلي على كفاءات الخدمة المصرفية دراسة حالة بنك الفلاحة و التنمية الريفية بالاغواط - رحمون صبرينة; حجاج هاجر فتيحة; بوخلخال خالد (جامعة عمار ثليجي الاغواط, 2022)
In this study, we will try to clarify the impact of internal marketing on the efficiency of the banking service at the Bank of Agriculture and Rural Development, Laghouat, by addressing the following problem: What are the effects of internal marketing on the efficiency of the banking service of the Bank of Agriculture and Rural Development? We have adopted a model consisting of two variables, the independent variable, and it has been divided into four independent sub-variables: motivation, training, empowerment, employee testing, internal communications, and the dependent variable. The following results were reached: The necessity of paying more attention to the application of the internal marketing program because of its significant impact on the efficiency of the banking service provided to customers.